Specyfika postrzegania historii własnego życia. Rozważania nad tekstami autobiograficznymi J.-J. Rousseau - Winkler, Marta (Hybris, 2015)
Autobiographical memory is a specific kind of memory concerning events and issues related to yourself. Your conception of your own life involves narratives in which all of yours experiences are interrelated. Autobiographical memory connects your present self with your past experiences (that’s why it’s important for theories about continuity of self). In this article I will analyse autobiographical texts of French philosopher Jean-Jacques Rousseau in the context of autobiographical memory theories.